TAXATION FOR GENDER EQUALITY: PROPOSAL OF MEASURES FOR THE REPUBLIC OF SERBIA ON THE ROAD TO EUROPEAN INTEGRATION - Ivanov, Iva (Pravni zapisi, 2020)
Gender equality in the Republic of Serbia has still not been reached. The female unemployment rate is 11,1% and the inactivity rate is more than 50% which endagers the sustainable development for the Republic of Serbia. Even though the problem has been recognized, adequate measures have still not been taken to address it. For that reason, this paper provides an analysis of the need for economic empowerment of women in the Republic of Serbia, as well as the adequacy of tax measures to achieve such a goal, based on which six fiscal measures are proposed in this paper. The measures proposed are aimed at the economic empowerment of women, primarily through their employment and encouragement to use their property rights, which entail a number of other positive effects on the position of women. The measures proposed are tax breaks aimed at encouraging flexible work arrangements (part-time work and work "from home"), as well as the possibility of provision of child-care services for employees. Also, an increase in the tax burden for making gifts consisting of a share on agricultural land by a female to a male family member is proposed.